Thymus pulegioides L. as a rich source of antioxidant, anti-proliferative and neuroprotective phenolic compounds. Issue 7 (29th June 2018) - Taghouti, Meriem; Martins-Gomes, Carlos; Schäfer, Judith; Félix, Luis M.; Santos, João A.; Bunzel, Mirko; Nunes, Fernando M.; Silva, Amélia M.
Abstract : The potential of Thymus pulegioides L. as an alternative and valuable source of functional ingredients has been assessed. Abstract : The potential of Thymus pulegioides L. as an alternative and valuable source of functional ingredients has been assessed. For this purpose, the phenolic constituent profiles and the antioxidant, anti-proliferative, neuroprotective, anti-aging and anti-diabetic activities of both T. pulegioides aqueous decoctions (AD) and hydro-ethanolic extracts (HE) were studied and compared for the first time. Rosmarinic acid was the main phenolic compound, accounting for 35.2% or 47.8% of total identified phenols in AD or HE, respectively (58.5 and 151.9 mg g −1 extract). Furthermore, large amounts of luteolin- O -hexuronide (AD: 39.9 ± 2.5 mg g −1, HE: 60.8 ± 7.0 mg g −1 ), eriodictyol- O -hexuronide (AD: 19.9 ± 2.5 mg g −1, HE: 26.8 ± 7.0 mg g −1 ) and chrysoeriol hexoside (AD: 23.5 ± 0.7 mg g −1, HE: 16.0 ± 0.7 mg g −1 ) were found. Both extracts showed significant in vitro antioxidant activity and anti-proliferative activity against Caco-2 cells (IC50 82.25 μg mL −1 and 105.44 μg mL −1, AD and HE, respectively), and reduced hepatotoxicity (HepG2 cells). In general, both T. pulegioides extracts showed poor anti-diabetic activity, moderate anti-aging effects and high neuroprotective activity with both AD and HE extracts, at 0.5 mg mL −1, showing 80% inhibition of the acetylcholinesterase activity and 94% inhibition of the tyrosinase activity. The present study highlights the important potential of this herb as a functional food ingredient.